2013
DOI: 10.1093/alcalc/agt050
|View full text |Cite
|
Sign up to set email alerts
|

µ-Opioid Receptor Gene (OPRM1) Polymorphism A118G: Lack of Association in Finnish Populations with Alcohol Dependence or Alcohol Consumption

Abstract: Aims: The molecular epidemiological studies on the association of the opioid receptor µ-1 (OPRM1) polymorphism A118G (Asn40Asp, rs1799971) and alcohol use disorders have given conflicting results. The aim of this study was to test the possible association of A118G polymorphism and alcohol use disorders and alcohol consumption in three large cohort-based study samples. Methods: The association between the OPRM1 A118G (Asn40Asp, rs1799971) polymorphism and alcohol use disorders and alcohol consumption was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
(81 reference statements)
2
17
0
Order By: Relevance
“…Nevertheless, the psychosocial support was highly appreciated by participants based on participants' qualitative evaluation of the treatment (not reported here). The OPRM1 A118G allele and genotype frequencies of the PG participants were similar to those reported earlier in the Finnish population [28] . Even though no evidence of OPRM1 A118G polymorphism's association with PG diagnosis compared to healthy controls was observed, it cannot be excluded that the lack of association in our data could be due to the low power of our sample to detect small effects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the psychosocial support was highly appreciated by participants based on participants' qualitative evaluation of the treatment (not reported here). The OPRM1 A118G allele and genotype frequencies of the PG participants were similar to those reported earlier in the Finnish population [28] . Even though no evidence of OPRM1 A118G polymorphism's association with PG diagnosis compared to healthy controls was observed, it cannot be excluded that the lack of association in our data could be due to the low power of our sample to detect small effects.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, 6% of the samples were re-sequenced with the second set of primers to confirm that sequencing had no error. For genetic case-control association analysis, 506 previously genotyped (98 females) participants [28] free of mood, anxiety and substance use disorders according to DSM-IV were used as controls.…”
Section: Oprm1 A118g Genotypingmentioning
confidence: 99%
“…In studies of opioid dependence, results have been mixed, with the minor (G) allele reported to have no effect in some studies (Crowley et al 2003; Levran et al 2008; Nelson et al 2014; Nikolov et al 2011) and to decrease risk in others (Bond et al 1998; Tan et al 2003). Similarly, analyses of alcohol dependence have reported increased risk (Bart et al 2005; Kim et al 2004), no effect (Bergen et al 1997; Rouvinen-Lagerstrom et al 2013; Sander et al 1998; Xuei et al 2007), and decreased risk (Schinka et al 2002; Town et al 1999) for this allele. Analyses of rs1799971 with other addictive substances also show no consensus (Clarke et al 2013; Crist and Berrettini 2013; Franke et al 2001; Gelernter et al 1999; Hardin et al 2009; Munafo et al 2013).…”
Section: Introductionmentioning
confidence: 95%
“… References: a (Nikolov et al 2011); b (Stallings et al 2005; Stallings et al 2003); c (Nelson et al 2014; Nelson et al 2013); d (Maher et al 2011); e (Carter et al 2008; Cinciripini et al 2006; Cinciripini et al 2005; Lam et al 2012; Minnix et al 2011; Robinson et al 2007; Robinson et al 2011); f (Edenberg 2002; Edenberg et al 2010); g (Saccone et al 2009a; Saccone et al 2009b); h (Aromaa and Koskinen 2004; Rouvinen-Lagerstrom et al 2013); i (Bierut et al 2010; Bierut et al 2008); j (Broms et al 2012; Kaprio et al 2002); k (Kamens et al 2013); l (Frank et al 2012; Treutlein et al 2009); m (Levran et al 2008); n (Iacono et al 1999; Keyes et al 2009; McGue et al 2007; Miller et al 2012); o (Loukola et al 2008; Saccone et al 2007); p (Loukola et al 2008); q (Elliott et al 1985; Elliott et al 1989; Hoft et al 2009); r (Andrews et al 2003); s (Van den Oord et al 2006); t (David et al 2011); u (Nikolov et al 2011); v (Hops et al 2000); w (Weiss et al 2008); x (Chen et al 2009; Kendler et al 2007; …”
Section: Figurementioning
confidence: 99%
“…Of particular interest is the µ-receptor, which has been linked to the brain reward areas and increases in reinforcement to drinking alcohol, albeit inconsistently (Rouvinen-Lagerstrom et al, 2013). In addition to the opioid system, it has long been known that variations in alcohol metabolism are associated with different levels of risk of an AUD yet this knowledge is rarely applied to clinical practice (Eriksson, 2001;Cook et al, 2005;Wall et al, 2005).…”
Section: Introductionmentioning
confidence: 99%